Potential of Propolis for Diabetic Wound Healing: A Literature Review - Sukmana, Mayusef; Rasyid, Muhammad; Paramita, Swandari; Yasir, Yadi; Wahyuningsih, Sri (Open Access Health Scientific Journal, 2025)
Background: Diabetes mellitus, a chronic metabolic disorder often leads to impaired wound healing, a serious complication resulting in diabetic ulcers, infections and even amputations. Conventional treatments for diabetic wounds can be costly and have side effects. Propolis, a natural resinous substance collected by honeybees from various plants, has long been recognized for including antibacterial, anti-inflammatory, antioxidant, and immunomodulatory properties. This literature review aims to summarize and analysed the scientific evidence regarding the potential of propolis in accelerating wound healing in diabetic conditions.Methods: Google Scholar, PubMed, Science Direct, EBSCO, Watase UAKE and Proquest using relevant keywords including "propolis," "wound," "diabetic ulcer,". The selected articles included original research studies only that discussed the potential of propolis in diabetic wound healing. Inclusion criteria were articles published in English and specifically addressing the effects of propolis on wound healing in diabetic patients, randomised clinical trial sampling technique and the article published in 2015-2025.Results: The article search process found in Google Scholar are 184 articles, PubMed are 10 articles, Science Direct are 185 articles, EBSCO are one article, and Watase UAKE is one article and ProQuest are 721 articles. There were 2 articles that met the inclusion criteria. The article discussed the potential and relationship of propolis with Erythema and Exudates, White Blood Cell (WBC) Count and ESR, Ulcer Discharge, Surrounding Erythema, Wound healing, connective tissue formation, oxidative stress markers, inflammatory markers, HbA1c level.Conclusion: Propolis, as a natural product, offers a potential alternative or complementary treatment to conventional therapies. affects wound healing through a complex process erythema and exudates, White Blood Cell (WBC) Count and ESR, ulcer discharge, surrounding erythema, wound healing, connective tissue formation, oxidative stress markers, inflammatory markers, HbA1c level. This is a new strategy for managing diabetic foot ulcers.